2018
DOI: 10.5350/bmb20180730075415
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin’s lymphoma as a rare cause of vanishing bile duct syndrome: a case report

Abstract: Our study aimed to assess the correlation between the measured PiCCO® parameters and extubation time and intensive care unit (ICU) length of stay in patients who underwent coronary artery bypass grafting (CABG) surgery and were managed by monitorization of cardiac output and cardiac performance parameters with PiCCO®. Method: This study was conducted by retrospective analysis data of all 44 patients who underwent CABG surgery during December 2015-March 2016 and were managed through PiCCO® monitorization. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…VBDS is characterized by the disappearance of bile ducts, with the progressive damage resulting in cholestasis. 3 Prior evidence implies on the state of disease progression, which ultimately leads to hepatic failure. Earlier, patients with HL-related VBDS have been reported to have poor prognosis and overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…VBDS is characterized by the disappearance of bile ducts, with the progressive damage resulting in cholestasis. 3 Prior evidence implies on the state of disease progression, which ultimately leads to hepatic failure. Earlier, patients with HL-related VBDS have been reported to have poor prognosis and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that levels of bilirubin are reliable laboratory markers when compared with ALP, in the evaluation of response to treatment. 3 Ebadi et al's 21 study shows that, along with curative chemotherapy, tumor-directed radiotherapy, when used as a bridge in HL-associated VBDS (for lesions above the diaphragm), results in an improvement of liver function. However, the authors 21 could not measure the amount of tumor cytoreduction necessary to diminish the paraneoplastic liver damage and in turn permit the regeneration of the bile duct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations